The Effect of Estrogen Replacement Therapy on Alzheimer's Disease and Parkinson's Disease in Postmenopausal Women: A Meta-Analysis - Song, Yu-jia; Li, Shu-ran; Li, Xiao-wan; Chen, Xi; Wei, Ze-xu; Liu, Qing-shan; Cheng, Yong (Frontiers in Neuroscience, 2020)
Background: Estrogen replacement therapy (ERT) is a common treatment method for menopausal syndrome, however, its therapeutic value for the treatment of neurological diseases is still unclear. Epidemiological studies were performed and the effect of postmenopausal ERT on treating neurodegenerative diseases, including Alzheimer's disease (AD) and Parkinson's disease (PD), was summarized by meta-analysis. Methods: 21 articles were selected by systematical searching of contents enlisted on PubMed and Web of Science before June 1, 2019. Epidemiological studies were extracted and relevant research data was obtained from the original articles based on the predefined inclusion criteria and data screening principles. The Comprehensive Meta-Analysis Version 2 software was used to pool effective size, test heterogeneity, conduct meta-regression and subgroup analysis, and calculate publication bias. Results: Our results showed that ERT significantly decreased the risk of onset and/or developing of AD (OR: 0.672; 95% CI: 0.581-0.779; P﹤0.001) and PD (OR: 0.470; 95% CI: 0.368-0.600; P﹤0.001) compared with the control group. Subgroup and meta-regression analysis showed that study design and measure of effect were the source of heterogeneity. Age, sample size, hormone therapy ascertainment, duration of the treatment or route of administration did not play a significant role in affecting the outcome of the meta-analysis. Conclusion: We presented evidence here to support the use of estrogen therapy for the treatment of AD and PD.